Work motivation and associated factors among health workers in Bac Giang province in 2024: A cross-sectional study - Nhan, Nguyen Thi; Thu, Nguyen Thi Hoai; Giang, Nguyen Hoang Thu; My Anh, Bui Thi (Tạp chí Nghiên cứu Y học, 2025)
Work motivation is crucial for healthcare workers’ performance and the overall effectiveness of the health systems. A well-motivated healthcare workforce can lead to improved patient satisfaction, reduced errors, and a more sustainable health system. This study aimed to describe the work motivation of healthcare workers in Bac Giang province in 2024 and analyze associated factors. A cross-sectional descriptive study was conducted among 253 health workers in Bac Giang province, Viet Yen and Yen Dzung districts using a quantitative approach with structured questionnaire. The main findings revealed that 80.6% of respondents were categorized as having low work motivation, with an average score of 3.66 (SD = 0.37). Significant associations were observed between work motivation and workplace location, years of working in the health field, and night shift frequency. Particularly, workers at the commune level exhibited the highest motivation (55.1%), compared to the district (24.5%) and provincial levels (20.4%). Similarly, workers with more than 10 years of working in the health field were more likely to have high motivation (91.8%) than those with 10 years or less (8.2%). Night shift frequency also highly associated to motivation, with workers taking more than eight shifts per month showing significantly higher odds of motivation (OR = 4.76, 95% CI: 1.22 - 18.65, p = 0.025). These findings highlight the importance of targeted strategies to improve motivation, such as providing tailored incentives, addressing workplace disparities, and offering support to less experienced workers.